2017
DOI: 10.1080/04353676.2017.1285203
|View full text |Cite
|
Sign up to set email alerts
|

Change in geometry of a high Arctic glacier from 1948 to 2013 (Austre Lovénbreen, Svalbard)

Abstract: The change of Austre Lovénbreen, a 4.5 km 2 land-based glacier along the west coast of Spitsbergen, is investigated using geodetic methods and mass balance measurements over 1948 . For 2008, annual mass balances computed on 36-stake measurements were obtained, in addition to annual mass balances reconstructed from the neighbouring glaciers, Midtre Lovénbreen (1968Lovénbreen ( −2007 and Austre Brøggerbreen (1963Brøggerbreen ( −1967. The mean rate of glacier retreat for 1948-2013 is −16.7 ± 0.3 m a −1 . Fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…Wang et al analysis of glacier terrain, another study showed that the Pedersenbreen glacier, which is near AL, had experienced a marked retreat in 1936, 1990(Ai et al 2013). Similar to nearby studied glaciers in the area, AL experienced a pronounced retreat from 1948 to 2013: the total retreat was 1064 ± 20 m in length and 1.82 ± 0.28 km 2 in area (Marlin et al 2017). GPS observations indicated that the maximum ice-flow velocity along the glacier centre line of AL was 3.8 m a -1 from 2005 to 2010 and that the mean velocity of all observed stakes was 2.4 m a −1 during this period (Ai, .…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Wang et al analysis of glacier terrain, another study showed that the Pedersenbreen glacier, which is near AL, had experienced a marked retreat in 1936, 1990(Ai et al 2013). Similar to nearby studied glaciers in the area, AL experienced a pronounced retreat from 1948 to 2013: the total retreat was 1064 ± 20 m in length and 1.82 ± 0.28 km 2 in area (Marlin et al 2017). GPS observations indicated that the maximum ice-flow velocity along the glacier centre line of AL was 3.8 m a -1 from 2005 to 2010 and that the mean velocity of all observed stakes was 2.4 m a −1 during this period (Ai, .…”
supporting
confidence: 73%
“…Estimating the impact of each and every factor is extremely difficult, so we used a backtracking simulation to verify modelling results with measured values. Using the historical meteorological records ( Førland et al 2011), together with the data of past glacier terrain (Marlin et al 2017), a backtracking simulation from 1962 to 2009 was performed to verify the feasibility of the model. In this simulation, the model parameters (b = 0.05, E = 0.865) and the bedrock terrain were assumed to be unchanged in the past 50 years.…”
Section: Simulation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these geomorphological processes, the gradual disappearance of the glacier front is highly visible and is clearly a trigger of downstream dynamics. The strongest values reach around −28 m of height loss since 1995, which is consistent with glacier mass balance measurements (Friedt et al, ; Marlin et al, ). This wide vacuum created by the melting is actually a new area where both outflows and runoff are in reconfiguration.…”
Section: Resultssupporting
confidence: 87%
“…The aim of this research deals with short-term climatic events that have been identified as typical response mechanisms of contemporary rapid climate variations (Dyurgerov & Meier, 2000;Marlin et al, 2017;Nowak & Hodson, 2013;Oerlemans, 2005). More precisely, the goal is to investigate dynamics at the interface between the glacier front and the proglacial moraine.…”
Section: Introductionmentioning
confidence: 99%